Method of local linear approximation in the theory of bounded solutions of nonlinear differential equations - Slyusarchuk, V. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
The conditions for the existence of solutions of nonlinear differential equations in a space of functions bounded on the axis are established by using local linear approximations of these equations.